2018
DOI: 10.1021/acscatal.8b01398
|View full text |Cite
|
Sign up to set email alerts
|

Insulator Layer Engineering toward Stable Si Photoanode for Efficient Water Oxidation

Abstract: The ultrathin insulator layer in the silicon metal–insulator–semiconductor (MIS) photoanode plays important roles in determining the performance of water oxidation. We report that an insulator oxide electroforming phenomenon that occurred during long-term oxygen evolution reaction testing under constant external voltage is the primary reason for the degradation of the silicon MIS photoanode. Compared with TiO2, ZrO2 exhibits high electro-reduce resistance, which minimizes the cation transport in the dielectric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…These include SiO 2 ,28–41 TiO 2 ,42–47 HfO 2 ,48,49 Al 2 O 3 ,42,50–53 SrTiO 3 ,54 and ZrO 2. 55 Initially, MIS systems were motivated by their ability to improve the chemical stability of semiconductors, but recently many design strategies have been identified to improve the efficiency of these systems. In general, a large barrier height, low resistance, and ideal interfaces with minimal defects are necessary to achieve high efficiencies and photovoltages in MIS systems.…”
Section: Introductionmentioning
confidence: 99%
“…These include SiO 2 ,28–41 TiO 2 ,42–47 HfO 2 ,48,49 Al 2 O 3 ,42,50–53 SrTiO 3 ,54 and ZrO 2. 55 Initially, MIS systems were motivated by their ability to improve the chemical stability of semiconductors, but recently many design strategies have been identified to improve the efficiency of these systems. In general, a large barrier height, low resistance, and ideal interfaces with minimal defects are necessary to achieve high efficiencies and photovoltages in MIS systems.…”
Section: Introductionmentioning
confidence: 99%
“…During OER operation, TiO 2 deposited on photoanode degrades. [ 121–123 ] Electron conductivity strongly depends on the TiO 2 structure. [ 122 ] Amorphous compact layers deposited at moderate temperatures (100–200 °C) are almost insulators.…”
Section: Protection Layermentioning
confidence: 99%
“…Chemically stable, refractory oxide 1–3 nm thin films as HfO 2 [ 129 ] and ZrO 2 [ 121 ] have been used as a protection layer for photoanodes, using Ni or NiFe as OER catalyst, respectively. A comparison of only 2 nm thin TiO 2 and ZrO 2 , shows that TiO 2 of such low thickness is damaged by oxide electro‐reduction and Ti dissolution caused under OER conditions.…”
Section: Protection Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Si-NPls are quite attractive structures that have shown wider absorption and enhanced performance due to the clear increment of their active surface. 11,12 However, as photoanode, bare Si suffers from fast degradation and corrosion in aqueous environments, which dramatically limits its operation time 13 Several strategies based on the introduction of protective coatings to hinder surface passivation have been proposed to extend the lifetime of Si based photoanodes 14,15 Additional studies have shown the advantages of TiO2 or ZnO coatings on the performance of Si-NPls, [16][17][18] due to their optical tunability, 6 mechanical reinforcement, 10,19 and high photoactive performance. 6,10 Recently, photoactive junctions of precious metals and semiconducting materials have shown enhanced carrier transport capabilities of photogenerated electrons which could provide a more efficient catalytic performance for water splitting [20][21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%